The Flouting of Maxims Related to Its Implicature in Comic Strips - Jaufillaili, Jaufillaili (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2013)
Humors are often used in a communication process. It is usually use as medium for conveying mesages as well as themselves in more objective ways. Since humors contain some specific messages, most of them usually break the rule of Maxim created by Grice. This article highlights the maxim broke by humors.